Fundamentals of convolutional coding - Johannesson, Rolf, 1946-; Zigangirov, K. Sh.; IEEE Communications Society; IEEE Information Theory Society; Vehicular Technology Society (New York : Institute of Electrical and Electronics Engineers, 2015)
Fundamentals of Convolutional Coding, Second Edition, regarded as a bible of convolutional coding brings you a clear and comprehensive discussion of the basic principles of this field. Two new chapters on low-density parity-check (LDPC) convolutional codes and iterative coding. Viterbi, BCJR, BEAST, list, and sequential decoding of convolutional codes. Distance properties of convolutional codes.
Fundamentals of Convolutional Coding -- Introduction -- Convolutional Encoders-structural Properties -- Distance Properties of Convolutional Codes -- Decoding of Convolutional Codes -- Random Ensemble Bounds for Decoding Error Probability -- List Decoding -- Sequential Decoding -- Lowdensity Parity-Check Codes -- Turbo Coding -- Convolutional Codes with Good Distance Properties -- Minimal Encoders -- Wald's Identity.
Sponsors include "IEEE Communications Society; IEEE Information Theory Society; IEEE Vehicular Technology Society."
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed May 29, 2015)
Keywords: Coding theory; Convolutions (Mathematics); Error-correcting codes (Information theory); SCIENCE / System Theory; TECHNOLOGY & ENGINEERING / Operations Research; Coding theory; Convolutions (Mathematics).; Error-correcting codes (Information theory).; Coding theory; Convolutions (Mathematics); Error-correcting codes (Information theory); Electronic books